2020
DOI: 10.3390/molecules25122791
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of More Efficacious Curcumin Delivery Systems Using Colloid Science: Enhanced Solubility, Stability, and Bioavailability

Abstract: Curcumin is a bioactive constituent isolated from turmeric that has historically been used as a seasoning, pigment, and herbal medicine in food. Recently, it has become one of the most commonly studied nutraceuticals in the pharmaceutical, supplement, and food areas because of its myriad of potential health benefits. For instance, it is claimed to exhibit antioxidant, anti-inflammatory, antimicrobial, antiparasite, and anticancer activities when ingested as a drug, supplement, or food. Toxicity studies suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(94 citation statements)
references
References 141 publications
(199 reference statements)
2
92
0
Order By: Relevance
“…Moreover, curcumin exhibits antioxidant activity by regulating transcription factors and antioxidant enzymes, such as haem oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2), upregulating common antioxidative activities (superoxide dismutase (SOD) and glutathione (GSH)) and inhibiting cytokine production (e.g. interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α) and interleukin 12 (IL-12)) [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, curcumin exhibits antioxidant activity by regulating transcription factors and antioxidant enzymes, such as haem oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2), upregulating common antioxidative activities (superoxide dismutase (SOD) and glutathione (GSH)) and inhibiting cytokine production (e.g. interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α) and interleukin 12 (IL-12)) [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It is a good metal chelator, but previous studies have shown that curcumin-based metal complexes cause a decrease in their pharmacological action compared with free curcumin [ 34 ]. Curcumin can be protected from degrading factors by its encapsulation in various pharmaceutical formulations such as release systems based on natural and synthetic polymers, liposomes, micro/nanoemulsions, solid lipid nanoparticles [ 35 ]. Lipids associated with curcumin indeed increase bioavailability, but particles of this kind do not ensure a continuous, sustained release, even if the amount of immobilized curcumin is higher compared with biopolymers nanoparticles [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, curcumin (Cur) was utilized as a model bioactive substance due to its good activity, such as antioxidant, anticancer, antibacterial, and anti-inflammatory [ 15 ]. The use of curcuminoid is, however, extremely limited, owing to its poor water-solubility, easy chemical degradation, and low bioavailability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%